Antesedent brand loyalty pada kedai kopi di Jakarta - Effendi, Ricka Karlina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The objective of this study is to examine and analyze Influencing of Advertisement/Promotion and Social Network Service and Consumer Engagement and Brand Trust Through Brand Loyalty At Coffee Store At Jakarta. The samples being used in this study is 115 respondents. Data collection method that used in this study is purposive sampling. Hypothetical testing is conducted using Structuctural Equation Model (SEM). The findings of this study are: (1) Advertisement/Promotion has significance effect on consumer engagement, (2) Social network service has significance effect on consumer engagement, (3) Advertisement/Promotion has significance effect on brand trust, and (4) Social network service has significance effect on brand trust, (5) Customer engagement has positive effect on brand trust, (6) Consumer engagment has significance effect on brand loyalty, and (7) Brand trust has significance effect on brand loyalty